2015
DOI: 10.3390/antiox4040750
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of the Anti-Oxidant Capacity of Curcumin Glucuronides, the Major Curcumin Metabolites

Abstract: Curcumin metabolites namely curcumin monoglucuronide and curcumin diglucuronide were synthesized using an alternative synthetic approach. The anti-oxidant potential of these curcumin glucuronides was compared with that of curcumin using DPPH scavenging method and Oxygen Radical Absorbance Capacity (ORAC) assay. The results show that curcumin monoglucuronide exhibits 10 fold less anti-oxidant activity (DPPH method) and the anti-oxidant capacity of curcumin diglucuronide is highly attenuated compared to the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…But the poor oral bioavailability of curcumin contributed by its insolubility, instability, poor absorption, and rapid biotransformation has made it a typical class IV BCS molecule with poor pharmacokinetics [ 14 , 15 ]. A number of enhanced bioavailable formulations of curcumin as demonstrated by the enhanced plasma concentration of curcumin metabolites (glucuronide and sulfate conjugates of curcuminoids and their reduced forms) have been reported and are even available commercially [ 16 19 ]. However, recent studies demonstrated poor membrane permeability and lack of anti-inflammatory, antiproliferative, and antioxidant activities of curcumin glucuronides, the major metabolites of curcumin [ 15 , 20 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…But the poor oral bioavailability of curcumin contributed by its insolubility, instability, poor absorption, and rapid biotransformation has made it a typical class IV BCS molecule with poor pharmacokinetics [ 14 , 15 ]. A number of enhanced bioavailable formulations of curcumin as demonstrated by the enhanced plasma concentration of curcumin metabolites (glucuronide and sulfate conjugates of curcuminoids and their reduced forms) have been reported and are even available commercially [ 16 19 ]. However, recent studies demonstrated poor membrane permeability and lack of anti-inflammatory, antiproliferative, and antioxidant activities of curcumin glucuronides, the major metabolites of curcumin [ 15 , 20 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin has been used in traditional Chinese medicine for a long time in Taiwan, China and India ( 10 ). The pharmacological effects of curcumin include anti-amyloid ( 11 ), anti-bacterial ( 12 ), anti-depressant ( 13 ), anti-inflammatory ( 14 ), anti-oxidant ( 15 ), anti-diabetes ( 16 ) and anticancer properties ( 17 , 18 ). In addition, curcumin has been found to affect several anticancer signaling pathways such as inhibition of cancer cell proliferation ( 19 , 20 ) and induction of cell cycle arrest ( 21 ), apoptosis ( 22 ) or autophagy ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro study revealed that CUR-NP is solubilized in mixed micelles and the high solubilization capacity of CUR-NP leads to higher intestinal absorption of CUR following oral administration. Since CURG is less potent in terms of antioxidant activity and antitumor effects compared to CUR, 8,43 it is desirable to use a NP formulation that not only increases intestinal absorption but also decreases the metabolic degradation and conversion of CUR to other metabolites to further improve the bioavailability of CUR. Overall, additional in vitro and in vivo studies are needed to develop a better understanding of the absorption, metabolism, and overall effects of CUR and CUR-NP in the body.…”
mentioning
confidence: 99%